Co3O4 Hollow Nanoparticles and Co Organic Complexes Highly Dispersed on N‐Doped Graphene: An Efficient Cathode Catalyst for Li‐O2 Batteries. (29th January 2015) - Zhang, Zhang; Chen, Yanan; Bao, Jie; Xie, Zhaojun; Wei, Jinping; Zhou, Zhen
<x xml:space="preserve">Abstract</x> Rechargeable Li‐O2 batteries are promising candidates for electric vehicles due to their high energy density. However, the current development of Li‐O2 batteries demands highly efficient air cathode catalysts for high capacity, good rate capability, and long cycle life. In this work, a hydrothermal‐calcination method is presented to prepare a composite of Co3O4 hollow nanoparticles and Co organic complexes highly dispersed on N‐doped graphene (Co–NG), which acts as a bifunctional air cathode catalyst to optimize the electrochemical performances of Li‐O2 batteries. Co–NG exhibits an outstanding initial discharge capacity up to 19 133 mAh g−1 at a current density of 200 mA g−1. In addition, the batteries could sustain 71 cycles at a cutoff capacity of 1000 mAh g−1 with low overpotentials at the current density of 200 mA g−1. Co–NG composites are attractive as air cathode catalysts for rechargeable Li‐O2 batteries.